The relationship between corporate governance mechanisms and bank performance / Bernadette Josephine James - James, Bernadette Josephine (2015)
The high profile accounting scandals occurred in WorldCom and Enron as well as in the banking sectors, the Barings and Imarbank scandals, have deeply impacted the nation and world economies. These events had ignited the importance of implementing good corporate governance mechanisms for companies and the banking sectors throughout the countries including Malaysia. Therefore, in order to identify the specific corporate governance characteristics that would influence the nation and world economies, this dissertation examined corporate governance mechanisms specifically the ownership monitoring mechanism, internal control monitoring mechanism (board independence and board size), and regulatory mechanism (capital adequacy ratio) influence on the banks performance measured by return on assets (ROA) from the resource based theory perspective. Particular years chosen from 2009 until 2013 due to Bursa Malaysia listings requirement to disclose corporate governance practices in the annual report for all companies in Malaysia. Pearson correlation and the regression analysis methods have been adopted in this dissertation to accomplish the objectives. Based on the result, capital adequacy ratio found to be significant influence on return on assets as proxy for corporate performance. In addition, since the introduction of the Malaysian Code of Corporate Governance in 2000 until the revised version in 2012, from the descriptive analysis, banks in Malaysia did comply with the suggested recommendations particularly the number of members on the board requirements. Findings from this dissertation would assists the Central Bank of Malaysia and the Securities Commission to formulate strategies for the banking sector to be fully complied with the Malaysian Code of Corporate Governance 2012. In addition, banks in Malaysia would be able to identify which resources to be focused on in attaining higher corporte performance.